Analisis Perencanaan Produksi dengan Metode Agregat Planning pada Alicha Bakery Sragen (IJM: Journal of Multidisiplinary, 2025)
This study aims to analyze the production planning process at Alicha Bakery Sragen using the Aggregate Planning method to identify the most effective strategy in balancing production capacity, consumer demand, and cost efficiency. Alicha Bakery, as a business engaged in food production, especially bread, faces challenges in the form of demand and the perishable nature of products. Therefore, an appropriate production planning model is needed to prevent losses and optimally meet market needs. This study uses a quantitative descriptive approach by utilizing secondary data for the past five years, including data on production volume, demand volume, labor availability, effective working days, and production costs. Several aggregate planning strategies are evaluated, including the strategy level (constant production), chasing (production follows demand), and a mixed strategy (a combination of both). The analysis results indicate that a mixed strategy is the most optimal solution for Alicha Bakery. This strategy provides greater flexibility in adapting to changes in demand without significantly increasing inventory or labor costs. Implementing a mixed strategy also helps reduce overtime costs and mitigates the risk of overstocking or understocking.